Justice, Democracy, and Freedom in the Middle Ages: The Fables by Marie de France - Classen, Albrecht (Philosophy and Realistic Reflection, 2025)
It might be surprising, and yet it can certainly be confirmed that the Anglo-Norman poet Marie de France offered in her Fables (ca. 1190) a wide range of political, social, moral, and philosophical notions about the way people within her society should and could live together in a peaceful, just, and respectful manner. She did not question the foundations of feudalism or of monarchy, but she developed strong messages about ethical principles that should guide all individuals in their living together, irrespective of social classes, implying the close observation of privileges and obligations, responsibilities and duties to the collective. We do not find in Marie a social revolutionary; instead, she voices simply deep concerns about injustice, violation of the laws and the principles of ethics, and thus criticizes many shortcomings within her time, which all prove to be rather telling for our modern world, at least in the West. Although she was certainly not a revolutionary, she clearly signaled her deep concerns about the global problems and failures within her society, and this is rather contrary to most of our expectations of the medieval world. Drawing from her fables, we find ourselves in the unique opportunity to reflect on fundamental concerns in all human interactions, both in the past and the present. In short, as I will argue, her short verse narratives provide us with an amazing literary compass regarding conflicts and tensions, human desires, feelings, and values in all our lives, seen here through a medieval lens. We can even discover comments about the need for individual freedom, contrary to modern assumptions about the Middle Ages.